Fatty acid and tocochromanol patterns of some Turkish Boraginaceae - a chemotaxonomic approach - Bagci, E; Bruehl, L; Aitzetmuller, K; Altan, Y (Wiley, 2002)
The plant family Boraginaceae is known to produce a set of unusual fatty acids in the seed oils. In this study, the fatty acid, tocopherol, tocotrienol and plasto-chromanol-8 contents of some Onosma species (Onosma sericeum, O. armeniacum and O. polioxanthum) all belonging to sect. Onosma, Anchusa leptophylla subsp. leptophylla, Alkanna froedini and Paracaryum stenophyllum were determined. Some of the studied species are endemic for Turkey. While oleic, linoleic and alpha linolenic acid are the highest as usual fatty acids, gamma linolenic and stearidonic acids are more variable unusual fatty acids in studied genera patterns and the relative concentrations some of these fatty acids and partly also the tocochromanols in Boraginaceae seed oils are suggested to have chemotaxonomic value in this family. In particular, the presence or absence of chain elongation to erucic acid (22:1) and the presence or absence of Delta6-methylene-interrupted polyenoic acids such as gamma-linolenic and stearidonic acid are determined and marked as indicators of taxonomic relationship.
Keywords: Gamma-Linolenic Acid; Seed Lipids; Tocopherols; Antioxidants; Search; Oils